Transitioning into the workforce during the COVID-19 pandemic: Understanding the experiences of student diagnostic radiographers. Issue 1 (February 2022) - Blackburn, N.E.; Marley, J.; Kerr, D.P.; Martin, S.; Tully, M.A.; Cathcart, J.M.
Abstract: Introduction: The COVID-19 pandemic, with associated pressures on healthcare services and workforce, had implications for final year Diagnostic Radiography students completing their training and transitioning into employment. The aim of this study was to explore their experience as novice practitioners starting work and integrating into the workforce during a time of national crisis. Methods: Five early career Diagnostic Radiographers, eligible to join the temporary HCPC register, were recruited. One to one interviews were completed online exploring their thoughts, feelings and experiences. Participants had the option of using photographs to aid communication. Results: Interviews were transcribed, emerging themes identified and coded. Four main themes emerged specifically related to the COVID-19 pandemic, (i) perceived challenges associated with joining the workforce, (ii) managing expectations and unexpected outcomes during transition, (iii) adapting to changes in systems and structures, (iv) sense of uncertainty relating to professional identity. The impacts were experienced beyond the work environment into social and personal lives. Participants demonstrated resilience as they adapted to their shifting lives and drew on the support of clinical colleagues and University academics for help. They did report feelings of concern and anxiety. The participants all expressed a sense of feeling valued and supported in their new roles. Conclusion: The Pandemic was unprecedented and created uncertainty in terms of workforce requirements. This study highlights the personal impact and professional responses of novice practitioners, who felt a sense of duty and care to help support the NHS and others. Implications for practice: This will help in the understanding of the transition of student into employment and what wider support needs to be in place prior, during and after this phase.